Training undergraduate biomedical science majors in peer review and constructive criticism through a senior capstone course - Kelly J. Collins (Journal of Microbiology & Biology Education)
ABSTRACT Effective scientific communication is crucial for undergraduate students to succeed in future graduate or professional careers in the biomedical sciences. Peer review and constructive criticism are essential to producing written science communications. Unfortunately, training in how to perform peer review and incorporate constructive criticism is minimal in undergraduate science courses. Here, I describe a senior thesis course for immunology and microbiology majors that encourages students to integrate iterative peer review to improve their writing skills and their ability to incorporate feedback. In this course, students are expected to complete one of the following written projects that focuses on an immunological disorder or infectious disease: a research proposal, a case study, or a meta-analysis/systematic review. Each project is separated into six assignments, and each assignment is assessed through specifications (SPECS)-based grading and peer review where students have multiple attempts to improve their scores on each assignment. Approximately 40% of each student’s grade is based on their ability to incorporate feedback from peers and instructors. Preliminary survey results suggest that students are eager to learn how to effectively incorporate peer and instructor feedback. Enhancing training in peer review will encourage students to embrace constructive criticism, which will be essential for their future careers. Initial findings indicate that students are positively engaging with the peer-review process, and the use of SPECS grading fosters a growth mindset. Continued research will further explore how this method can enhance students’ confidence and skill in integrating feedback into professional scientific communication.